2007
DOI: 10.1007/s10750-007-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of an invasive population of the red swamp crayfish (Procambarus clarkii) in a Mediterranean wetland

Abstract: This study analyzes the population structure and dynamics of an invasive population of Procambarus clarkii (Girard, 1852) in a Mediterranean wetland using the Bhattacharya's and Von Bertallanfy's analytical methods. The main purpose was to collect biological data necessary for the management of this nuisance species. A maximum of five age classes were identified for both sexes, three of which being composed of a few or zero individuals. Age classes were classified into two subgroups--spring (SpL) and summer (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
65
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 25 publications
(30 reference statements)
14
65
3
3
Order By: Relevance
“…CL ∞ and k were estimated for each sex from the obtained 1 mm size-frequency distributions within the ELEFAN I module (non-parametric scoring of the VBGF fit) in the FAO-ICLARM Stock Assessment Tools software (FiSAT 2 v.1.2.2; Pauly and David, 1981;Gayanilo and Pauly, 1997;Scalici et al, 2010), and t 0 was assessed by non-linear regression analysis. Longevity (t max ) was estimated by t max = (3/k) + t 0 (Gayanilo and Pauly, 1997;Scalici and Gherardi, 2007). Finally, the growth performance index (φ ) was derived from k and CL ∞ by applying the equation φ = log(k) + 2 log(CL ∞ ) (Pauly and Munro, 1984).…”
Section: > Growth and Life-history Traitsmentioning
confidence: 99%
“…CL ∞ and k were estimated for each sex from the obtained 1 mm size-frequency distributions within the ELEFAN I module (non-parametric scoring of the VBGF fit) in the FAO-ICLARM Stock Assessment Tools software (FiSAT 2 v.1.2.2; Pauly and David, 1981;Gayanilo and Pauly, 1997;Scalici et al, 2010), and t 0 was assessed by non-linear regression analysis. Longevity (t max ) was estimated by t max = (3/k) + t 0 (Gayanilo and Pauly, 1997;Scalici and Gherardi, 2007). Finally, the growth performance index (φ ) was derived from k and CL ∞ by applying the equation φ = log(k) + 2 log(CL ∞ ) (Pauly and Munro, 1984).…”
Section: > Growth and Life-history Traitsmentioning
confidence: 99%
“…Longevity (t max ) was estimated using the equation t max = (3/k) + t 0 , and mean lifetime (t 1/2 ) was estimated using the equation t 1/2 = {Σ[n(t)·t]}/N, where n is the number of individuals at time t and N the total number of individuals (Gayanilo and Pauly, 1997;Scalici and Gherardi, 2007;Chucholl, 2011). The growth performance index (ø´) was derived from k and L ∞ by applying the equation ø´= log(k) + 2log (L ∞ ) (Pauly and Munro, 1984).…”
Section: > Life-history Analysismentioning
confidence: 99%
“…Furthermore, life-history data are crucial to develop population management or eradication strategies (cf. Scalici and Gherardi, 2007), especially when an IAS has become well established and early eradication has failed (Simberloff, 2003;Bufford and Daehler, 2011). Filipová et al (2011) recently demonstrated a considerable genetic divergence between European and North American cytochrome c oxidase subunit I (COI) gene fragment sequences of O. immunis.…”
Section: Introductionmentioning
confidence: 99%
“…Procambarus clarkii has all of these traits (Huner, 2002) and the species is well known for its ecological plasticity (Gutierrez-Yurrita and Montes, 1999; Alcorlo et al, 2004). Procambarus clarkii can even adapt to extreme environments, including temporary streams and polluted water (Scalici and Gheradi, 2007).…”
Section: A Warm-water Crayfish In a Temperate Environmentmentioning
confidence: 99%
“…In the Hampstead Heath ponds it appears that, as in Germany, that P. clarkii only breed once a year, with juveniles found in October (Richter, 2000). Procambarus clarkii is able to produce at least two generations a year in its native range (Huner, 2002) and in parts of its invasive range in southern Europe (Gherardi et al, 1999;Gherardi, 2006;Scalici and Gheradi, 2007). In optimal conditions, over 600 eggs per berried female have been observed (Huner, 2002) and even in cooler climates the mean number of eggs was 285 per female (Chucholl, 2011b).…”
Section: P5mentioning
confidence: 99%